Achilles Tendon Echo Intensity Changes Across a 5-Day Training Cycle in Elite Athletes - Salatkaite Urbone, Saule; Cesanelli, Leonardo; Kamandulis, Sigitas; Satkunskiene, Danguole (International Journal of Sports Medicine, 2025)
The aim of this study was to determine if a 5-day training cycle in professional sports team athletes caused acute and subacute alterations in Achilles tendon (AT) echo intensity (EI). The study included 24 men and 24 women of football, handball, and volleyball teams from the top national leagues. During their respective competition periods, eight players from each team were monitored in every training session over a 5-day training cycle. It involved monitoring AT EI, cross-sectional area with ultrasound, subjective feelings of fatigue, and perceived exertion throughout the training cycle. The results revealed a significant acute and subacute effect on EI at distal (p<0.001), middle (p<0.001), and proximal (p<0.001) AT locations. The acute effect had a significant impact on the subacute changes in EI at all locations (p<0.001). A significant interaction of athletes' biological sex, the acute effect was only observed in the distal AT (p=0.013). The study revealed a significant decrease in AT EI following team sports training sessions for men and women. A consistently reduced EI of the AT during the 5-day training cycle suggests that repetitive loading likely induces structural changes in the tendon.
Keywords: ultrasound; sports; grayscale; B-mode; Achilles tendon